EVALUASI PROGRAM KETERAMPILAN DI MADRASAH ALIYAH MENGGUNAKAN MODEL CIPPO - Umi Muzayanah (Balai Penelitian dan Pengembangan Agama Jakarta, 2021)
The existence of skills programs in non-vocational madrasah aliyah has actually been practiced for a long time in several madrasas. Along with the need for skills education in madrasah aliyah, the Ministry of Religion continues to open opportunities for madrasa aliyah to implement skills programs. Using qualitative methods, this study aims to evaluate the skills program at MAN 1 Surakarta and MAN 1 Karanganyar, Central Java. Evaluation is carried out on aspects of Context, Input, Process, Product, and Outcome (CIPPO). The results showed that the implementation of the skills program at MAN 1 Surakarta and MAN 1 Karanganyar was quite good. Of the five aspects evaluated, the product aspect received the lowest score compared to the other four aspects. This is because there is no certification of expertise from training institutions for graduates of skills programs, skills products do not yet have national standards, and there are still few alumni of skills programs who work or open businesses in accordance with the skills obtained in madrasas. Therefore, madrasah aliyah skills programs need to increase collaboration with training institutions and the industrial world to the issuance of certificates of expertise for graduates of skills programs and recruitment of workers from skills program alumni.